Effect of optimized new Shengmai powder on exercise tolerance in rats with heart failure by regulating the ubiquitin-proteasome signaling pathway - Wang, Shuai; Wang, Lin; Gu, Shaoke; Han, Yixiao; Li, Linfeng; Jia, Zhuangzhuang; Gao, Ning; Liu, Yu; Lin, Shanshan; Hou, Yazhu; Wang, Xianliang; Mao, Jingyuan (Frontiers in Cardiovascular Medicine, 2023)
Decreased exercise tolerance is a common symptom in patients with heart failure, which is closely related to protein degradation and apoptosis regulated by the ubiquitin-proteasome signaling pathway (UPS). In this study, the effect of Chinese medicine, optimized new Shengmai powder, on exercise tolerance in rats with heart failure was investigated via the UPS signaling pathway. The heart failure model was prepared by ligating the left anterior descending branch of the coronary artery in rats, in which the sham-operated group was only threaded without ligation. Rats (LVEF≤45%) were randomly divided into the model group, YHXSMS group, Benazepril group, and proteasome inhibitor Oprozomib group, and given the corresponding drugs by gavage for 4 weeks. The cardiac function of rats was evaluated by echocardiography examination and hemodynamic test and the exercise tolerance was done by exhaustive swimming test. The mechanism was revealed by TUNEL detection, immunohistochemistry, immunofluorescence analysis, Western blot, and quantitative real-time PCR. The results showed that the cardiac function and exercise tolerance of rats in the model group were decreased, along with the destruction of cardiac and skeletal muscle fibers, the proliferation of collagen tissue, and the increment of apoptosis. Our study suggested that optimized new Shengmai powder could exert anti-apoptotic effects on myocardial and skeletal muscle cells and improve myocardial contractility and exercise tolerance by inhibiting the over-activation of UPS signaling pathway, down-regulating MAFbx, and Murf-1 overexpression, inhibiting the activation of the JNK signaling pathway, up-regulating bcl-2 expression, and decreasing bax and caspase-3 levels. In conclusion, the study showed that optimized new Shengmai powder could improve cardiac function and exercise tolerance in rats with heart failure through the UPS signal pathway.